2003
DOI: 10.1079/phn2003517
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between low income and household food expenditure patterns in Canada

Abstract: Objectives: To compare food expenditure patterns between low

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(100 citation statements)
references
References 24 publications
8
89
1
2
Order By: Relevance
“…Unemployment status or paying monthly rent may lead to a cut food expenditures when there are limited resources (46)(47)(48) . Kirkpatrick and Tarasuk (46) found that among low-income households, households that paid rent or mortgages had lower food expenditures than those without housing payments. These findings imply that a multifaceted intervention approach, such as appropriate labour market programmes, unemployment benefits and housing subsidies, as well as food assistance programmes, may be helpful in alleviating food insecurity by making family resources more stable and sustainable.…”
Section: Discussionmentioning
confidence: 99%
“…Unemployment status or paying monthly rent may lead to a cut food expenditures when there are limited resources (46)(47)(48) . Kirkpatrick and Tarasuk (46) found that among low-income households, households that paid rent or mortgages had lower food expenditures than those without housing payments. These findings imply that a multifaceted intervention approach, such as appropriate labour market programmes, unemployment benefits and housing subsidies, as well as food assistance programmes, may be helpful in alleviating food insecurity by making family resources more stable and sustainable.…”
Section: Discussionmentioning
confidence: 99%
“…In France, the costs of more nutrient-dense, healthier diets have been found to be higher, whereas energy-dense diets high in fat and sugar continue to be a low-cost option (Drewnowski et al, 2004;Andrieu et al, 2006). Thus, when studying food habits including consumption of fruit and vegetables, disposable income can be assumed to have an effect, as access to, for example, fruit and vegetables may be constrained by low income (Giskes et al, 2002;Kirkpatrick and Tarasuk, 2003). This poses challenges for nutrition policies to improve the availability and supply of recommended foods for low-income people.…”
Section: T Lallukka Et Almentioning
confidence: 99%
“…In particular, high levels of these variables are associated to greater consumptions of low fat foods, high fibre foods, fruit and vegetables. Furthermore, low incomes and low education levels are generally related to high energetic intake (Billson, Pryer, & Nichols, 1999;Giskes, Turrell, Patterson, & Newman, 2002;Groth, Fagt, & Brondsted, 2001;Irala-Estevez et al, 2000;Kirkpatrick & Tarasuk, 2003;Ricciuto, Tarasuk, & Yatchew, 2006;Trichopoulou, Naska, & Costacou, 2002). An explanation is that low income levels can limit health-conscious behaviour.…”
Section: Socio-demographic Determinants Of Food Habitsmentioning
confidence: 99%